2021
DOI: 10.1002/pip.3401
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interconnection failure on photovoltaic module performance

Abstract: Understanding the impact of failures on performance is necessary for any technology's development. There are many interconnection schemes that have emerged as the field solar photovoltaics has matured, but the most commonly used and well‐understood scheme is ribbon tabbing. In the field, the contacts between the ribbons and the cell metallization can fail via corrosion or solder joint failure. Solder joint failures are simulated by systematically cutting the interconnections of four‐busbar, multicrystalline si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[22], [23] Dust Accumulation Environmental pollution [24], [25] Leaves fall, bird droppings Environmental pollution [25] Hot Spot Mechanical and optical degradation of encapsulation [33] Glass breakage Bad installation [27] Welding Leaching of silver or copper, solder joint fatigue, bad welding [28] Frame issues Snowing [27] Microcracks Multiple (transportation, incorrect installation, vibrations, excessive loads, environmental stress, improper cleaning, etc.) [34] Busbar failure Incorrect packaging, installation, hail, and/or stone throwing [35] Module degradation Multiple [36] Discoloration Multiple [37] Delamination Multiple [38] Cell breakage Multiple (production, transport, installation, vibrations, environmental stress, improper cleaning, and maintenance, etc.) [27], [39] Connection System…”
Section: Pv Modulementioning
confidence: 99%
“…[22], [23] Dust Accumulation Environmental pollution [24], [25] Leaves fall, bird droppings Environmental pollution [25] Hot Spot Mechanical and optical degradation of encapsulation [33] Glass breakage Bad installation [27] Welding Leaching of silver or copper, solder joint fatigue, bad welding [28] Frame issues Snowing [27] Microcracks Multiple (transportation, incorrect installation, vibrations, excessive loads, environmental stress, improper cleaning, etc.) [34] Busbar failure Incorrect packaging, installation, hail, and/or stone throwing [35] Module degradation Multiple [36] Discoloration Multiple [37] Delamination Multiple [38] Cell breakage Multiple (production, transport, installation, vibrations, environmental stress, improper cleaning, and maintenance, etc.) [27], [39] Connection System…”
Section: Pv Modulementioning
confidence: 99%
“…In contrast, although various composites have been suggested for bioresorbable interconnection materials [ [19] , [20] , [21] , [22] , [23] ], such materials are still difficult to utilize owing to their many limitations, including low electrical conductivity, poor processability, and mechanical instability. For example, when conductive polymers (CPs), such as poly (3,4-ethylenedioxythiophene) (PEDOT) and polypyrrole (PPy), are fused with bioresorbable polymers [ [21] , [22] , [23] ], they yield poor conductivities (<0.1 ​kS/m), which undermines the device electrical power and efficiency [ 24 , 25 ]. Furthermore, the resorption and biocompatibility of CPs are not well established [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, because these materials are designed for constructing planar electrical pathways, they have limitations to make physical binding and vertical interconnection. Consequently, owndrawbacks of prior bioresorbable interconnection materials degrade the performance of fully bioresorbable devices or make unstable connection sites [ 24 ]. Therefore, solder or silver paste, which is not a resorbablematerial, is still used to prepare bioresorbable electronic device prototypes [ 30 , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%
“…Process‐induced shunts, recombination, and cracks within a cell also affect I 02 , n 2 , R sh parameters 6,7 . Cracks, finger breakages, busbar interconnect failure, and corrosion increase cell and overall module R s 8,9 . Boron‐oxygen defects formation in a bulk region, aging of cell material affects I 01 , n 1 parameters 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Rajput et al have proposed the method that extracts cell I 01 and R s from the EL images and estimates module output using SDM 24 . Colvin et al, 8 Kropp et al, 25 and Kikelj et al 26 have reported methods to estimate the performance of a module suffering from R s ‐related defects such as cracks, busbar interconnects failure, corrosion, finger breakages. However, these methods have been developed considering only R s ‐defects without the coexistence of other types of defects and degradation.…”
Section: Introductionmentioning
confidence: 99%